Term of Ummiy in Hadith: Measuring Contextual Meaning - Azis Arifin; Endad Musaddad; Sholahuddin Al Ayubi (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Understanding the meaning of ummiy in the hadith does not seem to be able to be done partially, because this will lead to misinterpretation of a hadith text containing the term. Understanding the meaning of ummiy in the hadith by highlighting aspects of language and history is an important option to do. This can be the basis for placing the meaning of ummiy as the material for the next study. This study aims to reveal the meaning of ummiy in the hadith inclusively and contextually. This research is qualitative in nature using linguistic and historical approaches, and the existing data is presented in an analytical descriptive manner. The results of this study reveal that the term ummiy in the hadith does not only have one meaning, but has multiple meanings. Based on the language aspect, the term ummiy can be interpreted as illiterate, people who are not blessed with books and people who have bad characteristics. Meanwhile, from a historical point of view, the term ummiy is interpreted as illiterate and a title for Arabs in general. Thus, the meaning of the term ummiy needs to be adapted to the context. This relates to the subject characterized by the term, in this case the Prophet himself and the Arabs in general.